2019
DOI: 10.17221/239/2018-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Influence of milling whole wheat grains and particle size on thermo-mechanical properties of flour using Mixolab

Abstract: Whole grain wheat flour (WG) of three different particles sizes (194.9, 609.4, and 830.0 µm) was prepared by milling whole grain. The effect of particle size on the thermo-mechanical properties of flour was investigated using Mixolab equipment and solvent retention capacity (SRC). The results showed that particle size influences the functionality of the gluten network. The SRC test revealed that the water absorption increased from 77.43% to 85.76%, with decrease in particle size. The C2 (protein weakening) val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 31 publications
4
12
0
2
Order By: Relevance
“…In order to obtain information on the rheological characteristics, the Mixolab technique can be taken into account since, in only one test, it can predict the quality of the finite product, simulating dough behavior in the bread-making process. The Mixolab technique has been used to assess the impact of different milling fractions from whole buckwheat grains on the rheological properties [30], as well as the effect of amaranth and quinoa milling fractions on wheat flour dough rheology [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…In order to obtain information on the rheological characteristics, the Mixolab technique can be taken into account since, in only one test, it can predict the quality of the finite product, simulating dough behavior in the bread-making process. The Mixolab technique has been used to assess the impact of different milling fractions from whole buckwheat grains on the rheological properties [30], as well as the effect of amaranth and quinoa milling fractions on wheat flour dough rheology [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…In previous research works, wet gluten and dry gluten were significantly correlated with water absorption whereas gluten index had significant correlation with dough stability time and dough development time of wheat varieties retaining bread making potential [15]. A study reflected that whole wheat flour of coarser particles affect gluten network and baking properties [16]. Similarly positive correlation was recorded between wet gluten content and sensory attributes of crackers [17].…”
Section: Discussionmentioning
confidence: 84%
“…They found that grinding wheat with such an MC leads to an increase in grain temperature, which has a negative influence on the flour properties [8]. Other authors produced whole wheat flour from grain with MCs of 15% [21] and 16% [22]. They found that coarse particles had a negative influence on the gluten network and flour baking quality, whereas research conducted by [23] showed that multistage milling of dried wheat (about 8% moisture) without tempering allows wholegrain flour with better baking quality than wholegrain flour from tempered wheat (about 16%) to be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…According to their study, wheat grain with low MCs (e.g., 10-12%) produced adequate quality wholemeal flour. However, the mentioned authors [8,[21][22][23][24] did not study the grinding energy requirements.…”
Section: Introductionmentioning
confidence: 99%